Evaluation of the Repeatability and Accuracy of RTK GNSS under Tree Canopy - Eren, Mehmet; Kurtulgu, Zumrut; Pirti, Atinc (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Using the Real Time Kinematic (RTK) GNSS (Global Navigation Satellite Systems) Method, one may precisely estimate a location on Earth in “real-time” to within a few centimeters. However, significant limitations remain, such as accuracy loss due to poor satellite sight (e.g., high satellite obstructions from tree canopy and dense urban areas). It usually takes time to resolve the ambiguities or, on many occasions, results in failure. Several satellite systems have been deployed in recent years besides GPS and GLONASS, such as Galileo, BeiDou, and other satellite systems. GNSS is the replacement word for GPS, GLONASS, Galileo, and BeiDou. Theoretically, this GNSS system would be more beneficial than previous systems such as GPS; issues with decreased position accuracy and limited satellite visibility (for example, in the presence of a tree canopy) may be resolved. This study aims to reduce integer ambiguity resolution time using RTK GNSS and examine RTK GNSS’s repeatability/accuracy in forested areas. The outcomes of GNSS positioning (compared with total station) in this study clearly showed improvement because of observing many satellites. The results suggest that the RTK GNSS system is preferred for surveying forested areas. This situation increases the accuracy of the RTK GNSS measurements and shortens the solution time for integer ambiguity. The horizontal component accuracy obtained in repeated RTK GNSS surveys in the forested areas remains 1–12 cm. Keywords: accuracy, GNSS, precision, repeatability, Real Time Kinematic, tree canopy